PENGARUH PENGEMBANGAN KARIER, KESEHATAN KERJA DAN KOMUNIKASI TERHADAP KINERJA PERSONEL MILITER DAN PNS KESEHATAN KOSTRAD - Priyo Susilo; Widodo Nugroho (JMB : Jurnal Manajemen dan Bisnis, 2017)
The aim in this study is to analyze the influence of Career Development,Health and Communications working on the Performance of militarypersonnel and civil servants in Kostrad Health corps. The method usedin this research is explanatory research that aims to make it clearinfluence between the variables through statistical analysis. The studypopulation was military personnel and civil servants in Kostrad Healthcorps, amounted to 112 people. This research sample totaled 53people, stratified random sampling method is used for sampling.Hypothesis Testing done in advance through the validity and reliabilitytests continued to the basic assumptions test and Classical Assumptiontest.The Results of this study show that each variable careerdevelopment, occupational health and Communications is positive andsignificant impact on the performance of military personnel and civilservants in Kostrad Health corps. Together that career development,occupational health and communication have significantly positive effecton the Performance of military personnel and civil servants in KostradHealth corps. And the results of this study showed that the higheroccupational health variables influence on the performance of militaryand civil servants in Kostrad Health corps. It can be concluded that theperformance of military personnel and civil servants in Kostrad Healthcorps will increase if Career Development, Health and Communicationswork is also getting better.